An Audit of Visual Acuity using a Snellen chart for Residents in a Care home, aged 65years or over - Ward, Hannah (2012)
Background: Visual impairment (VI) is highly prevalent, but currently remains untreated and preventable in Britain‟s older population (Evans, Fletcher, Wormald et al. 2002). Eighty percent of all VI can be avoided or treated (WHO, 2011). People in residential or nursing homes are at a higher risk of having their eye problems overlooked (Pols, Bates, McGraw et al. 2000). Aim: To conduct an audit of visual acuity (VA), a measure of VI against a national standard, the British Geriatric Society (BGS, 2010) standard, which states that all older people should be assessed for VI and a VA of 6/12 or less (using the Snellen chart) denotes VI. Methods: Mixed methods study, quantitative methods to measure and analyse VA and qualitative questionnaire to objectively comment on the resident‟s visual history. Sample consisted of all care home residents aged 65 years or older, excluding residents due to ethical reasons. Results: 24/25 (96%) residents scored a VA of 6/12 and below, so have VI according to the BGS. Majority of men and women have mild to moderate VI. Conclusion: VI is highly prevalent in my particular care home, but there is a regular ophthalmic service in-place which implies that VI is rarely undetected. It is recommended that this audit is repeated for all older people (hospital/care homes/persons own home), with standardised VI terminology, VI categories and using the ETDRS tool rather than the Snellen. This audit can be used to guide nurses to improve their risk assessment and identification, which they can use to maximise patient/resident safety.